The Role of Islamic Education Teachersin Implementing Problem Based Learning to Improve Students' Understanding in Islamic Education Subject: A Case Study at SMK Swadhipa 2 Natar - Dewi, Ika Yunita; Jalaluddin; Baharudin (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in implementing the Problem Based Learning (PBL) model and its impact on student understanding. This study uses a descriptive qualitative approach implemented at SMK Swadhipa 2 Natar. The research subjects consisted of PAI teachers as the main informants and Grade 11 TKJ 1 students as supporting informants. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing. In testing the validity of the data, triangulation was used, with triangulation techniques and triangulation sources. The results of the study indicate that PAI teachers play an important role as facilitators and motivators in the implementation of the Problem Based Learning model. Teachers design contextual problems, organize discussion activities, guide group investigations, and provide motivation and reinforcement to students during the learning process. The implementation of PBL can encourage students to be more active, critical, and involved in PAI learning. Student understanding has increased, especially in the ability to explain material, relate concepts to everyday life, and conclude the Islamic values ​​​​learned. However, the implementation of PBL still faces several obstacles, such as differences in student engagement and limited learning time. The role of Islamic Religious Education teachers in implementing the Problem-Based Learning model has positively contributed to improving student understanding. This research is expected to serve as a reference for teachers in developing innovative and contextual Islamic Religious Education learning strategies